Determinants and timing of lifestyle changes in postmenopausal breast cancer survivors: A longitudinal qualitative study - Sandra J. M. van Cappellen – van Maldegem; Anja de Kruif; Jacob C. Seidell; Lonneke V. van de Poll – Franse; Floortje Mols; Meeke Hoedjes (PLoS ONE, 2025)
Background Adopting and maintaining favorable lifestyle changes can be challenging for postmenopausal breast cancer (PMBC) survivors. Understanding their experiences and needs can help tailor lifestyle support throughout their care journey. Purpose This qualitative study explored 1) perceived determinants relevant for favorable lifestyle change among PMBC survivors, 2) the needs and preferences of PMBC survivors regarding lifestyle support, and 3) perceived determinants relevant for preferred timing of lifestyle support among PMBC survivors. Methods A total of 42 in-depth longitudinal interviews were conducted at one year (n = 24) and 1.5 years (n = 21) following a breast cancer diagnosis. Data were analyzed using thematic analysis. Results Our analysis revealed 12 main themes: 1) 3 themes describe determinants that may affect the process of favorable lifestyle change (type of lifestyle behavior, previous attempts to change lifestyle, comorbidities), 2) 3 themes express PMBC survivors’ needs for lifestyle support from health care professionals (HCPs) (need for information, need for activation by lifestyle support, need for effective communication by HCPs), 3) 6 themes describe determinants influencing PMBC survivors’ preferred timing of addressing these needs (type of treatment, coping style, previous experience with cancer, personality, motivation for lifestyle change, social support). Conclusions Lifestyle support should consider psychological and physical effects of breast cancer diagnosis and treatment, which may hinder some PMBC survivors’ ability to make favorable lifestyle choices. Our results suggest that HCPs should offer ongoing individualized lifestyle support throughout the care continuum to meet the varied needs of PMBC survivors.